The Factors Affecting the Access to Banking Credits of Family Businesses in Tra Vinh Province, Vietnam - Nguyen, Ha Hong (International Journal of Economics and Financial Issues, 2018)
The study on the factors affecting the access to banking credits of family businesses in Tra Vinh province by directing survey of 250 family businesses in 7 districts and 01 city in Tra Vinh province in which multivariable regression model has been used. The results show that the access to banking credits of family businesses depends on gender, education, years of experience, income, assets and social relations. Based on the results of the analysis, it could be proposed that a number of measures to improve the ability to borrow capital from credit institutions for family businesses and at the same time imply policies for commercial banks in the province. Tra Vinh can improve the ability to serve family businesses better in the future. Keywords: family businesses, credit institutions, banking credits, commercial banks, multi-variable regression JEL Classifications: G21, M1